A particle-reinforced aluminum-based composite material and a preparation method thereof

By using two aluminum alloy powders and nanoparticles with different melting points, combined with high-energy ball milling, ultrasonic dispersion and discharge plasma sintering and other technologies, the problems of aluminum-based composite materials in enhancing phase dispersion and interface bonding are solved, and high-performance and high-density aluminum-based composite materials are achieved.

CN116397141BActive Publication Date: 2025-05-02BEIHANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210494094.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-05
Publication Date
2025-05-02
Estimated Expiration
2042-05-05

AI Technical Summary

Technical Problem

The existing aluminum-based composite materials cannot meet the application needs of high-performance composite materials due to insufficient uniformity of enhanced phase dispersion, poor "reinforced phase/matrix" interface bonding, long preparation process, high preparation cost and low density.

Method used

Two aluminum alloy powders with different melting points are used as matrix materials, and microscale heterogeneous structure nanoparticles reinforced aluminum-based composite materials are prepared through high-energy ball mill mixing, ultrasonic dispersion of nanoparticles, vacuum drying and liquid-solid biphasic discharge plasma sintering.

Benefits of technology

Improves the dispersion uniformity of the enhanced phase and the "enhanced phase/matrix" interface binding capability, shortens the preparation process, reduces costs, and improves the density and performance of the material, including thermal conductivity and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116397141B_ABST
    Figure CN116397141B_ABST
Patent Text Reader

Abstract

The present invention relates to a particle-reinforced aluminum-based composite material and a preparation method thereof, and belongs to the field of metal material preparation and processing. The raw material composition of the composite material is: 6063, A7075, A6061 or A2024 aluminum alloy powder: 20-50 vol.%, AlSi10Mg, AlSi7Mg, Al‑12Si, A356 or A357 aluminum alloy powder: 50-80 vol.%. It also contains 0.01-1.0 wt.% of graphene oxide powder. The preparation method includes the steps of high-energy ball milling mixed bimetallic powder, ultrasonic dispersion of graphene oxide powder, ultrasonic stirring + mechanical stirring mixed powder, vacuum drying of powder mixture and liquid-solid two-phase discharge plasma sintering. Two aluminum alloy powders with different melting points are used as matrix materials, and nanographene is used as a reinforcing phase to achieve a composite reinforcement effect, thereby obtaining a structurally functional integrated aluminum-based composite material with excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a particle-reinforced aluminum-based composite material and a preparation method thereof, and belongs to the field of metal material preparation and processing. Background Art

[0002] Aluminum alloy has high specific strength, good ductility, and corrosion resistance. At the same time, its electrical and thermal conductivity are excellent. It is the most widely used metal material in the aerospace field. With the continuous improvement of the service conditions and performance requirements of various new high-performance aircraft, the performance of traditional aluminum alloy materials has entered a bottleneck of development, and its application has also been restricted. Nowadays, the gradually developed and mature aluminum-based composite materials have become the focus of people's attention. In particular, aluminum-based composite materials reinforced with nanophases are favored by researchers because of their small addition amount, light weight, high specific strength, high thermal conductivity and other characteristics. They are expected to obtain good comprehensive performance after being combined with traditional metal materials. Among them, the reinforcing phase represented by nanographene is considered to be one of the best choices for reinforcing aluminum-based composite materials because of its unique two-dimensional structure, extremely high strength and modulus, and good electrical and thermal conductivity. At present, it is usually prepared by hot isostatic pressing, spark plasma sintering, metal infiltration, stirring casting and in-situ reaction.

[0003] Limited by the characteristics of high specific surface area of ​​nanoparticles, easy agglomeration, and not resistant to high temperature erosion, there are still some problems and difficulties in the current composite material design and preparation process. For example, the invention of Chinese patent CN 106566942 A discloses a method for preparing high-performance graphene-enhanced aluminum-based composite materials, in which a mixed powder of graphene and aluminum powder is coated and hot-pressed, but the method has a relatively low melting point of aluminum powder, and there is still room for improvement in sintering wettability, and the hot-pressing sintering forming pressure cannot be effectively transmitted, and the prepared composite material interface joints often have microscopic defects, resulting in serious loss of thermal physical properties and mechanical properties of the composite material. In addition, for the characteristics of easy agglomeration and poor dispersibility of nano-enhanced phases, mechanical stirring is usually used. For example, the invention of Chinese patent CN 111515403 A adopts a mechanical stirring method to disperse graphene, but this method does not take into account the thermal effect generated during the dispersion process, which is bound to cause the effect of mechanical stirring to be greatly reduced. After the dispersion is completed, graphene will still form agglomerates in a short time. Summary of the invention

[0004] Based on the background that the existing composite material design and preparation methods are imperfect and cannot meet the growing application demand of high-performance composite materials, the present invention focuses on solving the problems of insufficient uniformity of reinforcement phase dispersion, poor "reinforcement phase / matrix" interface bonding, long preparation process, high preparation cost, low densification degree, etc. in current research and application of high-performance nanoparticle reinforced aluminum-based composite materials. In view of the problems existing in the existing preparation methods, a nanoparticle reinforced aluminum-based composite material and a preparation method thereof are proposed.

[0005] The present invention uses two kinds of aluminum alloy powders as matrix materials, one of which is Al6063 aluminum alloy powder with low alloy element content, which has the characteristics of high melting point and high thermal conductivity. The alloy powder is selected as the carrier and skeleton of the nanoparticle reinforcement phase during the subsequent semi-solid forming of the powder. Other alloys with the same characteristics are also applicable to the present invention, including A7075, A6061, A2024 and other alloy powders; the other is AlSi10Mg aluminum alloy powder with high Si element content, which has low melting point, good castability, and good thermal conductivity in molten or semi-molten state. Fluidity and formability. The alloy is selected as a binder for high melting point alloy powder and graphene during semi-solid powder forming. Other alloys with similar characteristics are also applicable to the invention, including AlSi7Mg, Al-12Si, A356, A357 aluminum alloys and intermediate alloy powders, etc.; in addition, nano-graphene oxide (GO) is used as a reinforcing (toughening) phase, which has the characteristics of high electrical conductivity, high thermal conductivity and high strength. Other nano-particle reinforcing phases with similar characteristics are also applicable to the invention, and nano-particles include carbon nanotubes, nano-silicon carbide particles, etc.

[0006] A particle-reinforced aluminum-based composite material, whose raw material composition is, in terms of volume percentage, 20-50 vol.% of one of 6063, A7075, A6061 and A2024 aluminum alloy powders, and 50-80 vol.% of one of AlSi10Mg, AlSi7Mg, Al-12Si, A356 and A357 aluminum alloy powders or intermediate alloy powders.

[0007] Preferably, the particle-reinforced aluminum-based composite material has the following raw material compositions, in terms of volume percentage: 6063 aluminum alloy powder: 20-50 vol.%, AlSi10Mg aluminum alloy powder: 50-80 vol.%.

[0008] Furthermore, the above-mentioned particle-reinforced aluminum-based composite material also contains graphene oxide powder (nanoparticles), carbon nanotube particles or nano silicon carbide particles, and the added amount is 0.01 to 1.0 wt.% of the total mass of the composite material (raw material); preferably 0.1 to 0.5 wt.%.

[0009] The material of the invention is a novel micro-scale heterogeneous structure nano-particle reinforced aluminum-based composite material.

[0010] Among them, the 6063 aluminum alloy powder has a purity of 99.5-99.9%, a particle size of 53-150 μm, a thermal conductivity of 201-218 W / (m·K), a melting point range of 616-654°C, and a density of 2.70-2.75 g / cm 3 The composition of 6063 aluminum alloy is preferably: Mg 0.50-1.00wt.%, Si 0.60-1.00wt.%, Cu≤0.35wt.%, Fe≤0.2wt.%, and the rest is Al; more preferably Al-0.65Mg-0.7Si-0.35Cu-0.2Fe. The volume fraction of Al6063 powder added to the composite material accounts for 20-50vol.%.

[0011] Among them, AlSi10Mg aluminum alloy powder has a purity of 99.5-99.9%, a particle size of 15-53 μm, a thermal conductivity of 105-122 W / (m·K), a melting point range of 557-596°C, and a density of 2.65-2.69 g / cm 3 The composition of the AlSi10Mg aluminum alloy is preferably: Si 6.50-14.5wt.%, Mg 0.10-0.80wt.%, and the rest is Al. The volume fraction of the AlSi10Mg powder added to the composite material is 50-80vol.%.

[0012] Among them, graphene oxide powder (GO) is brown-yellow powder, with a sheet diameter of 100-1000nm, a thickness of 1-3nm, an ash content of more than 2%, an oxygen content of 20-40%, a monolayer rate of ≥92%, and a thermal conductivity of 2000-3000W / (m·K). The mass fraction of graphene oxide nanoparticles added to the composite material accounts for 0.01-0.5wt.%.

[0013] A method for preparing a particle-reinforced aluminum-based composite material comprises the following steps:

[0014] (1) High-energy ball milling of mixed bimetallic powders

[0015] After cleaning and drying, 6063 aluminum alloy powder and AlSi10Mg aluminum alloy powder are placed in a high-energy ball mill according to the volume ratio and mixed. After the ball milling is completed, the ball and material are separated by a sieve to obtain a mixed dual alloy powder;

[0016] (2) Ultrasonic dispersion of graphene oxide powder

[0017] Adding graphene oxide powder into anhydrous ethanol, and dispersing the granular graphene oxide using an ultrasonic disperser to obtain a graphene oxide suspension;

[0018] (3) Ultrasonic stirring + mechanical stirring mixed powder

[0019] The dual alloy powder prepared in step (1) is directly added to the graphene oxide suspension obtained in step (2), and ultrasonic stirring is performed using an ultrasonic disperser; then, the mixture is stirred using a mechanical stirring propeller blade so that the dispersed graphene is adsorbed on the surface of the metal powder;

[0020] (4) Vacuum drying of powder mixture

[0021] The mixture prepared in step (3) is placed in a vacuum drying oven for drying, and then the obtained mixed powder is sieved to obtain a dual alloy mixed powder with graphene added;

[0022] (5) Liquid-solid dual-phase spark plasma sintering

[0023] The mixed powder dried in step (4) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology to obtain a micro-scale heterogeneous structure nanoparticle reinforced aluminum-based composite material.

[0024] In the above preparation method, in step (1), the abrasive selected for high-energy ball milling is stainless steel balls, the ball-to-material ratio is 5:1 to 20:1, anhydrous ethanol is added as a dispersant, the ball mill revolution speed is 50 to 200 r / min, and the ball milling time is 2 to 10 hours.

[0025] In step (2), the dispersion time of the graphene oxide powder is 10 to 60 minutes. During the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

[0026] In step (3), after adding the dual alloy powder to the graphene oxide suspension, ultrasonic stirring is performed using an ultrasonic disperser for 5 to 30 minutes. When the mixture is stirred using a mechanical stirring propeller blade, the stirring speed is 50 to 300 r / min and the stirring time is 5 to 60 minutes. During the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

[0027] In step (4), when the mixture is vacuum dried, the vacuum degree reaches ≤2×10 -4 MPa, the drying temperature is 60-100℃, and the drying time is 6-12h.

[0028] In step (5), during sintering, the sintering temperature is 480-600°C, the pressure is 30-100 MPa, and the sintering atmosphere is vacuum. In the micro-scale heterogeneous structure nanoparticle reinforced aluminum-based composite material, the micro-scale heterogeneous structure refers to a composite structure in which a low melting point phase tightly surrounds a high melting point phase in a micro-scale region (1-100 μm), which can also be called a micro-scale composite structure.

[0029] Beneficial effects:

[0030] (1) The present invention designs a micro-scale heterogeneous composite material matrix structure. By selecting two aluminum alloy powders with different melting points, during forming, one of the aluminum alloy powders with high melting point, high thermal conductivity and large particle size remains in a solid state and serves as a carrier of the nano-reinforced phase and the skeleton of the composite material. The other aluminum alloy powder with low melting point and small particle size is in a semi-molten state under the coupling field of pressure and temperature, and serves as a binder for the reinforcement phase and the skeleton. Since the selected low-melting point aluminum alloy is an aluminum alloy with a high silicon content, it has good fluidity and thixotropic properties. Under the action of thermal coupling, it can be filled into all gaps in the skeleton built by the high-melting point powder, thus overcoming the shortcomings of high porosity and low density of general powder metallurgy products. Similarly, other magnesium alloys, titanium alloys and high-temperature alloys with similar characteristics can also be applied to the present invention.

[0031] (2) The present invention designs a new type of high thermal conductivity composite material composition. It includes two aluminum alloys with the same structure but different components and a nano-reinforced phase. Among them, graphene as a nano-reinforced phase has very high electrical conductivity, thermal conductivity and strength, which can not only improve the toughness of the composite material, but also improve the thermal physical properties of the composite material to a certain extent. In addition, the selected two aluminum alloy combinations, due to the same crystal structure but different components, not only have good interface bonding ability, but also have high thermal conductivity and composite reinforcement effect, which can effectively improve the thermal physical properties of the composite material. Similarly, other high-performance nanoparticle reinforcement phases can also be applied to the present invention.

[0032] (3) The present invention utilizes an ultrasonic dispersion method to improve the uniformity of the reinforcement phase dispersion. Graphene powder and alloy mixed powder are dispersed. Since graphene has a very large specific surface area and is very easy to agglomerate, the general preparation method will weaken the reinforcement effect. Therefore, the organizational uniformity of the composite material is often a preparation difficulty. The present invention utilizes the cavitation effect of ultrasound to greatly improve the dispersion effect of graphene, and can completely disperse the agglomerated graphene powder into nanosheets, and also has a good stirring effect, thereby improving the uniformity of the mixed powder in the preparation of the composite material, and thus improving the organizational uniformity of the composite material. Moreover, unlike the general ultrasonic dispersion method, which damages the nano-reinforcement phase when the temperature continues to rise during use, the present invention adopts a dynamic cooling method to greatly improve the dispersion effect.

[0033] (4) The present invention combines vacuum spark plasma sintering with powder semi-solid rheology forming theory to improve the density of the composite material. Generally, the density of metal-based composite materials is one of the most critical indicators for evaluating the performance of composite materials. The higher the density, the denser the structure of the composite material, and the better the mechanical properties and functional characteristics. Based on the general spark plasma sintering forming, the present invention controls the forming temperature to the semi-solid temperature range of the selected low-melting point alloy, so that the second type of liquid phase sintering effect is obtained during the forming process, so that the liquid phase generated between the powder particles can evenly fill all the skeleton gaps, and under the action of pressure, the densification of the composite material is achieved, thereby obtaining a high-performance nanoparticle-reinforced metal-based composite material.

[0034] The present invention uses two aluminum alloy powders with different melting points as matrix materials, wherein one is an aluminum alloy powder with low alloy element content and high melting point, selects the alloy powder as the carrier and skeleton of the nanoparticle reinforcement phase during the subsequent powder semi-solid forming, and loads the nanoparticles into the matrix powder by ultrasonic dispersion and mechanical stirring, and serves as a nanoparticle carrier in the powder semi-solid forming process. At the same time, by a high-energy ball milling powder mixing method, another aluminum alloy powder with a low melting point and good casting performance with high melting point powder is mixed, and the good fluidity and formability thereof in a molten state or a semi-molten state are utilized as a binder for the high melting point alloy powder and the nanoparticle reinforcement phase during the mixed powder semi-solid forming. In addition, nanographene is used as the reinforcement (toughening) phase, and the reinforcement phase has the characteristics of high electrical conductivity, high thermal conductivity and high strength, so as to play a composite reinforcement effect, and obtain a structural function integrated aluminum-based composite material with excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the preparation process of the particle reinforced aluminum-based composite material of the present invention;

[0036] Figure 2 The present invention is a flowchart of the preparation process of the particle-reinforced aluminum-based composite material. DETAILED DESCRIPTION

[0037] The product protected in the present invention is a novel micro-scale heterogeneous structure nanoparticle reinforced aluminum-based composite material and its preparation method. Its raw material composition includes:

[0038] (1) 6063 aluminum alloy powder, purity 99.5-99.9%, particle size 53-150 μm, thermal conductivity 201-218 W / (m·K), melting point range 616-654°C, density 2.70-2.75 g / cm 3, wherein the alloy elements are as follows: Mg element is preferably 0.50-1.00wt.%; Si element is preferably 0.60-1.00wt.%; Cu element is preferably ≤0.35wt.%; Fe element is preferably ≤0.2wt.%. The volume fraction of Al6063 powder added to the composite material is 20-50vol.%. (Al-0.65Mg-0.7Si-0.35Cu-0.2Fe)

[0039] (2) AlSi10Mg aluminum alloy powder, purity 99.5-99.9%, particle size 15-53 μm, thermal conductivity 105-122 W / (m·K), melting point range 557-596°C, density 2.65-2.69 g / cm 3 The alloy elements are as follows: Si element is preferably 6.50-14.5 wt.%; Mg element is preferably 0.10-0.80 wt.%. The volume fraction of AlSi10Mg powder added to the composite material is 50-80 vol.%.

[0040] (3) Graphene oxide nanoparticles (GO), brown-yellow powder, flake diameter 100-1000 nm, thickness 1-3 nm, ash content>2%, oxygen content 20-40%, monolayer rate ≥92%, thermal conductivity 2000-3000 W / (m·K). The mass fraction of graphene oxide particles added to the composite material accounts for 0.01-1.0 wt.%, preferably 0.1-0.5%.

[0041] Based on the novel micro-scale heterogeneous structure nanoparticle reinforced aluminum matrix composite material designed by the present invention, a new preparation method is designed on this basis. The preparation process is as follows: Figure 1 and 2 shown.

[0042] Step 1: High-energy ball milling of mixed bimetallic powders

[0043] The selected aluminum alloy powders of Al6063 and AlSi10Mg are cleaned and dried, and then mixed in a high-energy ball mill according to a certain volume ratio. The abrasive selected for the high-energy ball mill is stainless steel balls, the ball-to-material ratio is 5:1-20:1, and anhydrous ethanol is added as a dispersant. The ball mill revolution speed is 50-200r / min, and the ball milling time is 2-10h. After the ball milling is completed, the ball and material are separated by a sieve, and the mixed dual alloy powder is collected for later use.

[0044] Step (2): Ultrasonic dispersion of nanoparticle reinforcement phase - graphene oxide powder

[0045] A certain amount of graphene oxide powder is added to anhydrous ethanol, and the granular graphene oxide is dispersed by an ultrasonic disperser to obtain a graphene oxide suspension, and the dispersion time is 10 to 60 minutes. During the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

[0046] Step (three): Ultrasonic stirring + mechanical stirring to mix the powder

[0047] The dual alloy powder prepared in step (a) is directly added to the graphene oxide suspension obtained in step (b), and ultrasonic stirring is continued using an ultrasonic disperser for 5 to 30 minutes. Then, the mixture is stirred using a mechanical stirring propeller blade at a stirring speed of 50 to 300 r / min for 5 to 60 minutes, so that the dispersed graphene is adsorbed on the surface of the metal powder, thereby obtaining the desired mixture. A cold water bath is used to physically cool the suspension container during the ultrasonic dispersion process.

[0048] Step (IV): Vacuum drying of powder mixture

[0049] Place the mixture prepared in step (iii) in a vacuum drying oven and set the vacuum degree to 2×10 -4 MPa, the drying temperature is 60-100°C, and the drying time is 6-12h. After drying, the obtained mixed powder is sieved to obtain the dual alloy mixed powder with added graphene, which is collected for later use.

[0050] Step (V): Liquid-Solid Dual-Phase Spark Plasma Sintering

[0051] The mixed powder dried in step (iv) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology. The sintering temperature is 480-600° C., the pressure is 30-100 MPa, and the sintering atmosphere is vacuum.

[0052] Embodiment 1:

[0053] Step 1: High-energy ball milling of mixed bimetallic powders

[0054] The selected aluminum alloy powders of Al6063 (Al-0.65Mg-0.7Si-0.35Cu-0.2Fe) and AlSi10Mg (Al-14Si-0.60Mg) were washed and dried with anhydrous ethanol, and then mixed in a high-energy ball mill at a volume ratio of 4:6. The abrasive selected for the high-energy ball mill was stainless steel balls, with a ball-to-material ratio of 10:1. Anhydrous ethanol was added as a dispersant, the ball mill revolution speed was 100r / min, and the ball milling time was 4.5h. After the ball milling was completed, the ball and material were separated using a sieve, and the mixed dual alloy powder was collected for later use.

[0055] Step (2): Ultrasonic dispersion of graphene oxide powder

[0056] 0.1% of the total weight of the raw materials was added to anhydrous ethanol, and the granular graphene oxide was dispersed by an ultrasonic disperser to obtain a graphene oxide suspension for 30 minutes. During the ultrasonic dispersion process, a cold water bath was used to physically cool the suspension container.

[0057] Step (three): Ultrasonic stirring + mechanical stirring to mix graphene and aluminum alloy powder

[0058] The dual alloy powder prepared in step (a) is directly added to the graphene oxide suspension obtained in step (b), and ultrasonic stirring is continued using an ultrasonic disperser for 30 minutes. Then, the mixture is stirred using a mechanical stirring propeller blade at a stirring speed of 100 r / min for 30 minutes, so that the dispersed graphene is adsorbed on the surface of the metal powder to obtain the desired mixture. A cold water bath is used to physically cool the suspension container during the ultrasonic dispersion process.

[0059] Step (IV): Vacuum drying of powder mixture

[0060] Place the mixture prepared in step (iii) in a vacuum drying oven and set the vacuum degree to 2×10 -4 MPa, the drying temperature is 60°C, and the drying time is 12h. After drying, the obtained mixed powder is sieved to obtain the dual alloy mixed powder with added graphene, which is collected for later use.

[0061] Step 5: Semi-solid spark plasma sintering of bimetallic powder

[0062] The mixed powder dried in step (iv) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology at a sintering temperature of 520° C., a pressure of 45 MPa, and a vacuum atmosphere.

[0063] Embodiment 2:

[0064] Step 1: High-energy ball milling of mixed bimetallic powders

[0065] The selected aluminum alloy powders of Al6063 (Al-0.65Mg-0.7Si-0.35Cu-0.2Fe) and AlSi10Mg (Al-14Si-0.60Mg) were washed and dried with anhydrous ethanol, and then mixed in a high-energy ball mill at a volume ratio of 4:6. The abrasive selected for the high-energy ball mill was stainless steel balls, with a ball-to-material ratio of 10:1. Anhydrous ethanol was added as a dispersant, the ball mill revolution speed was 100r / min, and the ball milling time was 4.5h. After the ball milling was completed, the ball and material were separated using a sieve, and the mixed dual alloy powder was collected for later use.

[0066] Step (2): Ultrasonic dispersion of graphene oxide powder

[0067] 0.5% of the total weight of the raw material graphene oxide powder is added to anhydrous ethanol, and the granular graphene oxide is dispersed by an ultrasonic disperser to obtain a graphene oxide suspension, and the dispersion time is 30 minutes. During the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

[0068] Step (three): Ultrasonic stirring + mechanical stirring to mix graphene and aluminum alloy powder

[0069] The dual alloy powder prepared in step (a) is directly added to the graphene oxide suspension obtained in step (b), and ultrasonic stirring is continued using an ultrasonic disperser for 30 minutes. Then, the mixture is stirred using a mechanical stirring propeller blade at a stirring speed of 100 r / min for 30 minutes, so that the dispersed graphene is adsorbed on the surface of the metal powder to obtain the desired mixture. A cold water bath is used to physically cool the suspension container during the ultrasonic dispersion process.

[0070] Step (IV): Vacuum drying of powder mixture

[0071] Place the mixture prepared in step (iii) in a vacuum drying oven and set the vacuum degree to 2×10 -4 MPa, the drying temperature is 60°C, and the drying time is 12h. After drying, the obtained mixed powder is sieved to obtain the dual alloy mixed powder with added graphene, which is collected for later use.

[0072] Step 5: Semi-solid spark plasma sintering of bimetallic powder

[0073] The mixed powder dried in step (iv) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology at a sintering temperature of 520° C., a pressure of 45 MPa, and a vacuum atmosphere.

[0074] Embodiment 3:

[0075] Step 1: High-energy ball milling of mixed bimetallic powders

[0076] The selected aluminum alloy powders of Al6063 (Al-0.65Mg-0.7Si-0.35Cu-0.2Fe) and AlSi10Mg (Al-14Si-0.60Mg) were washed and dried with anhydrous ethanol, and then mixed in a high-energy ball mill at a volume ratio of 4:6. The abrasive selected for the high-energy ball mill was stainless steel balls, with a ball-to-material ratio of 15:1. Anhydrous ethanol was added as a dispersant, the ball mill revolution speed was 150r / min, and the ball milling time was 5h. After the ball milling was completed, the ball and material were separated using a sieve, and the mixed dual alloy powder was collected for later use.

[0077] Step (2): Ultrasonic dispersion of graphene oxide powder

[0078] 1.0% of the total weight of the raw materials was added to anhydrous ethanol, and the granular graphene oxide was dispersed by an ultrasonic disperser to obtain a graphene oxide suspension, and the dispersion time was 20 minutes. During the ultrasonic dispersion process, a cold water bath was used to physically cool the suspension container.

[0079] Step (three): Ultrasonic stirring + mechanical stirring to mix graphene and aluminum alloy powder

[0080] The dual alloy powder prepared in step (a) is directly added to the graphene oxide suspension obtained in step (b), and ultrasonic stirring is continued using an ultrasonic disperser for 10 minutes. Then, the mixture is stirred using a mechanical stirring propeller blade at a stirring speed of 200 r / min for 20 minutes, so that the dispersed graphene is adsorbed on the surface of the metal powder to obtain the desired mixture. A cold water bath is used to physically cool the suspension container during the ultrasonic dispersion process.

[0081] Step (IV): Vacuum drying of powder mixture

[0082] Place the mixture prepared in step (iii) in a vacuum drying oven and set the vacuum degree to 2×10 -4 MPa, the drying temperature is 60°C, and the drying time is 12h. After drying, the obtained mixed powder is sieved to obtain the dual alloy mixed powder with added graphene, which is collected for later use.

[0083] Step 5: Semi-solid spark plasma sintering of bimetallic powder

[0084] The mixed powder dried in step (iv) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology at a sintering temperature of 560° C., a pressure of 60 MPa, and a vacuum atmosphere.

[0085] Embodiment 4:

[0086] Step 1: High-energy ball milling of mixed bimetallic powders

[0087] The selected aluminum alloy powders of Al6063 (Al-0.65Mg-0.7Si-0.35Cu-0.2Fe) and AlSi10Mg (Al-14Si-0.60Mg) were washed and dried with anhydrous ethanol, and then mixed in a high-energy ball mill at a volume ratio of 4:6. The abrasive selected for the high-energy ball mill was stainless steel balls, with a ball-to-material ratio of 20:1. Anhydrous ethanol was added as a dispersant, the ball mill revolution speed was 200r / min, and the ball milling time was 6h. After the ball milling was completed, the ball and material were separated using a sieve, and the mixed dual alloy powder was collected for later use.

[0088] Step (ii): vacuum drying of powder mixture

[0089] Place the bimetallic powder prepared in step (a) in a vacuum drying oven and set the vacuum degree to 2×10 -4 MPa, the drying temperature is 80°C, and the drying time is 10 h. After drying, the obtained mixed powder is sieved to obtain the dual alloy mixed powder without adding graphene, which is collected for later use.

[0090] Step (three): Semi-solid spark plasma sintering of bimetallic powder

[0091] The mixed powder dried in step (ii) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology at a sintering temperature of 540° C., a pressure of 45 MPa, and a vacuum atmosphere.

[0092] Comparative Example 1:

[0093] Step 1: High-energy ball milling of single metal powder

[0094] The selected grade Al6063 (Al-0.65Mg-0.7Si-0.35Cu-0.2Fe) aluminum alloy powder was washed with anhydrous ethanol and mixed in a high-energy ball mill. The abrasive selected for the high-energy ball mill was stainless steel balls, the ball-to-material ratio was 10:1, and anhydrous ethanol was added as a dispersant. The ball mill revolution speed was 100r / min, and the ball milling time was 4.5h. After the ball milling was completed, the ball and material were separated using a sieve, and the single alloy powder after ball milling was collected for later use.

[0095] Step (2): Ultrasonic dispersion of graphene oxide powder

[0096] 0.5% of the total weight of the raw material graphene oxide powder is added to anhydrous ethanol, and the granular graphene oxide is dispersed by an ultrasonic disperser to obtain a graphene oxide suspension, and the dispersion time is 30 minutes. During the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

[0097] Step (three): Ultrasonic stirring + mechanical stirring to mix graphene and aluminum alloy powder

[0098] The single alloy powder after ball milling in step (i) is directly added to the graphene oxide suspension obtained in step (ii), and ultrasonic stirring is continued using an ultrasonic disperser for 30 minutes. Then, the mixture is stirred using a mechanical stirring propeller blade at a stirring speed of 100 r / min for 30 minutes, so that the dispersed graphene is adsorbed on the surface of the metal powder, thereby obtaining the desired mixture. During the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

[0099] Step (IV): Vacuum drying of powder mixture

[0100] The mixture prepared in step (iii) was placed in a vacuum drying oven, and the vacuum degree was set to 2×10-4MPa, the drying temperature was set to 60°C, and the drying time was set to 12h. After drying, the obtained mixed powder was sieved to obtain a single alloy powder with graphene added, which was collected for later use.

[0101] Step 5: Semi-solid spark plasma sintering of single metal powder

[0102] The dried powder in step (iv) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology at a sintering temperature of 580° C., a pressure of 45 MPa, and a vacuum atmosphere.

[0103] Comparative Example 2:

[0104] Step 1: High-energy ball milling of single metal powder

[0105] The selected aluminum alloy powder of AlSi10Mg (Al-14Si-0.60Mg) was washed with anhydrous ethanol and then mixed in a high-energy ball mill. The abrasive selected for the high-energy ball mill was stainless steel balls, the ball-to-material ratio was 10:1, and anhydrous ethanol was added as a dispersant. The ball mill revolution speed was 100r / min, and the ball milling time was 4.5h. After the ball milling was completed, the ball and material were separated using a sieve, and the single alloy powder after ball milling was collected for later use.

[0106] Step (2): Ultrasonic dispersion of graphene oxide powder

[0107] 0.5% of the total weight of the raw material graphene oxide powder is added to anhydrous ethanol, and the granular graphene oxide is dispersed by an ultrasonic disperser to obtain a graphene oxide suspension, and the dispersion time is 30 minutes. During the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

[0108] Step (three): Ultrasonic stirring + mechanical stirring to mix graphene and aluminum alloy powder

[0109] The single alloy powder after ball milling in step (i) is directly added to the graphene oxide suspension obtained in step (ii), and ultrasonic stirring is continued using an ultrasonic disperser for 30 minutes. Then, the mixture is stirred using a mechanical stirring propeller blade at a stirring speed of 100 r / min for 30 minutes, so that the dispersed graphene is adsorbed on the surface of the metal powder, thereby obtaining the desired mixture. During the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

[0110] Step (IV): Vacuum drying of powder mixture

[0111] The mixture prepared in step (iii) was placed in a vacuum drying oven, and the vacuum degree was set to 2×10-4MPa, the drying temperature was set to 60°C, and the drying time was set to 12h. After drying, the obtained mixed powder was sieved to obtain a single alloy powder with graphene added, which was collected for later use.

[0112] Step 5: Semi-solid spark plasma sintering of single metal powder

[0113] The dried powder in step (iv) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology at a sintering temperature of 540° C., a pressure of 45 MPa, and a vacuum atmosphere.

[0114] Comparative Example 3:

[0115] Step 1: High-energy ball milling of mixed bimetallic powders

[0116] The selected commercial aluminum alloy powders of Al7075 and Al-7Si were cleaned and dried with anhydrous ethanol, and then mixed in a high-energy ball mill at a volume ratio of 4:6. The abrasive selected for the high-energy ball mill was stainless steel balls, the ball-to-material ratio was 10:1, and anhydrous ethanol was added as a dispersant. The ball mill revolution speed was 100r / min, and the ball milling time was 6.5h. After the ball milling was completed, the ball and material were separated using a sieve, and the mixed dual alloy powder was collected for later use.

[0117] Step (2): Ultrasonic dispersion of graphene oxide powder

[0118] 0.5% of the total weight of the raw material graphene oxide powder is added to anhydrous ethanol, and the granular graphene oxide is dispersed by an ultrasonic disperser to obtain a graphene oxide suspension, and the dispersion time is 30 minutes. During the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

[0119] Step (three): Ultrasonic stirring + mechanical stirring to mix graphene and aluminum alloy powder

[0120] The dual alloy powder prepared in step (a) is directly added to the graphene oxide suspension obtained in step (b), and ultrasonic stirring is continued using an ultrasonic disperser for 30 minutes. Then, the mixture is stirred using a mechanical stirring propeller blade at a stirring speed of 100 r / min for 30 minutes, so that the dispersed graphene is adsorbed on the surface of the metal powder to obtain the desired mixture. A cold water bath is used to physically cool the suspension container during the ultrasonic dispersion process.

[0121] Step (IV): Vacuum drying of powder mixture

[0122] The mixture prepared in step (iii) was placed in a vacuum drying oven, and the vacuum degree was set to 2×10-4MPa, the drying temperature was set to 60°C, and the drying time was set to 12h. After drying, the obtained mixed powder was sieved to obtain the dual alloy mixed powder with added graphene, which was collected for later use.

[0123] Step 5: Semi-solid spark plasma sintering of bimetallic powder

[0124] The mixed powder dried in step (iv) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology at a sintering temperature of 560° C., a pressure of 45 MPa, and a vacuum atmosphere.

[0125] Table 1 Summary of system composition, forming process and performance of examples and comparative examples

[0126]

[0127]

[0128] Through comparative analysis of experimental results, the thermal conductivity and mechanical properties of the dual alloy composite material with the addition of nanographene particles are significantly improved, especially with the increase of forming temperature and pressure, its density and thermal conductivity increase significantly. In addition, the strength and elongation of the material are further improved compared with those without the addition of graphene particles.

[0129] By comparing and analyzing with the comparative example, it can be seen that the composite material of the single alloy and the addition of nanographene particles has a thermal conductivity close to that of the alloy itself, and the density is lower than that of the composite material of the double alloy, indicating that the combination mode of the double alloy has a positive effect on improving the densification of the composite material. By comparing its mechanical properties, it can be seen that the double alloy combination has a promoting effect on the toughness of the material. In addition, compared with other grades of aluminum alloy combinations, the method described in the present invention is also applicable to other powder combinations.

Claims

1. A particle-reinforced aluminum-based composite material, characterized in that: According to volume percentage, the raw material composition is: 6063 aluminum alloy powder: 20~50vol.%, AlSi10Mg aluminum alloy powder: 50~80vol.%; The preparation steps are as follows: (1) High-energy ball milling of mixed bimetallic powders After cleaning and drying, 6063 aluminum alloy powder and AlSi10Mg aluminum alloy powder are placed in a high-energy ball mill according to a volume ratio and mixed. After high-energy ball milling, the ball and material are separated by a sieve to obtain a mixed dual alloy powder. (2) Ultrasonic dispersion of graphene oxide powder Adding graphene oxide powder into anhydrous ethanol, and dispersing the granular graphene oxide using an ultrasonic disperser to obtain a graphene oxide suspension; (3) Ultrasonic stirring + mechanical stirring mixed powder The dual alloy powder prepared in step (1) is added to the graphene oxide suspension obtained in step (2), and ultrasonic stirring is performed using an ultrasonic disperser; then, the mixture is stirred using a mechanical stirring propeller blade so that the dispersed graphene is adsorbed on the surface of the metal powder; (4) Vacuum drying of powder mixture The mixture prepared in step (3) is placed in a vacuum drying oven for drying, and then the obtained mixed powder is sieved to obtain a dual alloy mixed powder with graphene added; (5) Liquid-solid dual-phase spark plasma sintering The mixed powder dried in step (4) is placed in a graphite crucible and semi-solid powder is formed by spark plasma sintering technology to obtain a micro-scale heterogeneous structure nanoparticle reinforced aluminum-based composite material.

2. The particle-reinforced aluminum-based composite material according to claim 1, characterized in that: The particle-reinforced aluminum-based composite material also contains graphene oxide powder, carbon nanotube particles or nano silicon carbide particles, which account for 0.01-1.0wt.% of the total mass of the composite material.

3. The particle-reinforced aluminum-based composite material according to claim 2, characterized in that: 6063 aluminum alloy powder, purity is 99.5~99.9%, particle size is 53~150μm; AlSi10Mg aluminum alloy powder, purity is 99.5~99.9%, particle size is 15~53μm; graphene oxide powder flake diameter is 100~1000nm, thickness is 1~3nm.

4. The particle-reinforced aluminum-based composite material according to claim 3, characterized in that: In step (1), the abrasive of the high-energy ball mill is stainless steel balls, the ball-to-material ratio is 5:1-20:1, anhydrous ethanol is added as a dispersant, the ball mill revolution speed is 50-200 r / min, and the ball milling time is 2-10 h.

5. The particle-reinforced aluminum-based composite material according to claim 4, characterized in that: In step (2), the dispersion time of the graphene oxide powder is ultrasonically dispersed for 10 to 60 minutes; and during the ultrasonic dispersion process, a cold water bath is used to physically cool the suspension container.

6. The particle-reinforced aluminum-based composite material according to claim 5, characterized in that: In step (3), after adding the dual alloy powder to the graphene oxide suspension, ultrasonic stirring is performed using an ultrasonic disperser for a stirring time of 5 to 30 minutes; when the mixture is stirred using a mechanical stirring propeller blade, the stirring speed is 50 to 300 r / min and the stirring time is 5 to 60 minutes; A cold water bath was used to physically cool the suspension container during the ultrasonic dispersion process.

7. The particle-reinforced aluminum-based composite material according to claim 6, characterized in that: In step (4), when the mixture is vacuum dried, the vacuum degree is set to ≤2×10 -4 MPa, the drying temperature is 60~100℃, and the drying time is 6~12h.

8. The particle-reinforced aluminum-based composite material according to claim 7, characterized in that: In step (5), during sintering, the sintering temperature is 480-600°C, the pressure is 30-100 MPa, and the sintering atmosphere is vacuum.

Citation Information

Patent Citations

  • A method of preparing a high-performance graphene reinforced aluminium-based composite material

    CN106566942A

  • Method for preparing graphene reinforced aluminum matrix composite powder in short flow

    CN111515403A

  • Aluminum based composite material disk rotor

    JP1995144268A